Solve the system by substitution.

y, equals, minus, 2, x
y=
−2x
5, x, minus, 7, y, equals, minus, 38
5x−7y=
−38

1 answer

First, we substitute y with -2x in the second equation:

5x - 7(-2x) = -38
5x + 14x = -38
19x = -38
x = -38/19
x = -2

Now that we have the value of x, we can substitute it back into the first equation to find the value of y:

y = -2(-2)
y = 4

Therefore, the solution to the system of equations is x = -2 and y = 4.
Similar Questions
  1. Solve the system by substitution.minus, 2, y, minus, 10, equals, x −2y−10= x minus, 10, x, minus, y, equals, minus, 14
    1. answers icon 1 answer
  2. Solve the system by substitution.minus, 8, x, minus, 7, y, equals, minus, 5 −8x−7y= −5 minus, x, equals, y −x= y
    1. answers icon 1 answer
  3. Solve the system by substitution.minus, 5, x, minus, 9, y, equals, 33 −5x−9y= 33 minus, y, minus, 1, equals, x −y−1= x
    1. answers icon 1 answer
    1. answers icon 1 answer
more similar questions